2010
DOI: 10.1021/bm100999a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MonoPEGylated Human Galectin-2 by Small-Angle X-ray and Neutron Scattering: Concentration Dependence of PEG Conformation in the Conjugate

Abstract: Protein conjugation with polyethylene glycol (PEG) is a valuable means for improving stability, solubility, and bioavailability of pharmaceutical proteins. Using human galectin-2 (hGal-2) and 5 kDa PEG as a model system we first produced a PEG-hGal-2 conjugate exclusively at the Cys75 residue, resulting in two monosubstituted subunits per hGal-2 homodimer. Small angle X-ray and neutron scattering (SAXS and SANS) were combined to provide complementary structural information about the PEG-hGal-2 conjugate, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 46 publications
4
26
1
Order By: Relevance
“…They demonstrated that the shroud-like conformation is favored when the PEG molecular weight is higher than 10 kDa. Several other studies have been carried out to understand which configuration of PEG is favored when conjugated to proteins, yet a definite molecular picture has not clearly emerged.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the shroud-like conformation is favored when the PEG molecular weight is higher than 10 kDa. Several other studies have been carried out to understand which configuration of PEG is favored when conjugated to proteins, yet a definite molecular picture has not clearly emerged.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, based on these data, we propose a conformation of diPEG/Hb conjugates depending on two possible models, the "dumbbell" or "shroud" ones, with the latter corresponding to attached PEG chains wrapping around the protein and generating a "shielding" effect. 16,17 ■ EXPERIMENTAL SECTION Human Hemoglobin Preparation. Hb (approximately 64 000 g· mol −1 ) is a globular tetrameric protein constituted by two α and two β subunits.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Few studies have measured the conformation of PEGylated bioconjugates. Previous reports of the conformation of mPEG chains conjugated to proteins showed that the protein and polymer behave as two independent domains with little interaction. , …”
mentioning
confidence: 99%
“…Previous reports of the conformation of mPEG chains conjugated to proteins showed that the protein and polymer behave as two independent domains with little interaction. 3,4 Recent data indicate that advanced polymer architectures provide significant advantages in improving protein efficacy in vitro and in vivo. 5 Next-generation polymers for bioconjugation are often synthesized via controlled radical polymerization, typically yielding polymers with brush-type architectures with a variety of potential side chains.…”
mentioning
confidence: 99%